Hematologi Ikan Nila (Oreochromis niloticus) Yang Diberi Pakan Mengandung Larutan Biji Mangga Harum Manis (Mangifera indica L) - Putri, Ika Wahyuni; Laheng, Suardi; Puspita, Dila (Arborescent Journal, 2024)
Tilapia (Oreochromis niloticus), also known as tilapia, is one of the most common types of freshwater fish brought to several Asian countries, including Indonesia. Disease factors are obstacles in fish farming, and the emergence of diseases during fish farming is a danger that must always be anticipated. Harumanis mango seed solution is a material that can be used to protect and treat fish that are affected by disease. Harumanis mango seeds are natural ingredients that have the potential to increase the immune system. This study aims to determine the blood picture of tilapia (Oreochromis niloticus) fed with the addition of mango seed solution. It can be seen from the blood of tilapia, which shows the total number of erythrocytes, leukocytes, and hematocrit. The study was conducted from April to June 2024. The test fish were kept in Tambun Village, Baolan Village, and Tolitoli Regency. Then, the blood picture was analyzed at the Integrated Science Laboratory of Madako University, Tolitoli. The results of this study indicate that observations of the blood of tilapia fed with the addition of fragrant mango seed solution gave results that had a significant effect of P0.05 on total erythrocytes, total leukocytes, and hematocrit values. total erythrocytes (2,853,333.33 cells/mm3), leukocytes (29,000,000 cells/mm3), and hematocrit (12.53%) In this case, it is still a normal range value. Based on the study's results, it can be concluded that providing feed containing fragrant sweet mango seed solution has a positive impact on tilapia. This can be seen from the observed blood picture which is within the normal range.